2019
DOI: 10.1109/tbme.2018.2818300
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Feature Augmentation for Cardiac Ablation Target Learning From Images

Abstract: Abstract-Goal: We present a model-based feature augmentation scheme to improve the performance of a learning algorithm for the detection of cardiac radio-frequency ablation (RFA) targets with respect to learning from images alone. Methods: Initially, we compute image features from delayed-enhanced MRI (DE-MRI) to describe local tissue heterogeneities and feed them into a machine learning framework with uncertainty assessment for the identification of potential ablation targets. Next, we introduce the use of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Several studies used data-driven approaches with clinical data to characterize electrocardiogram signals measured on the body surface (Yaghouby et al, 2010 ; Rodrigues et al, 2017 ; Zhang et al, 2018 ; Petmezas et al, 2021 ). Sahli Costabal et al ( 2018 ) used a hybrid dataset approach to interpret activation times during AF and Lozoya et al ( 2019 ) showed how model-based feature augmentation can help to plan the targets for ablation therapy. We developed a detailed in silico setup as a perfectly controlled testing environment to understand intracardiac signals recorded with two different commercial catheters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies used data-driven approaches with clinical data to characterize electrocardiogram signals measured on the body surface (Yaghouby et al, 2010 ; Rodrigues et al, 2017 ; Zhang et al, 2018 ; Petmezas et al, 2021 ). Sahli Costabal et al ( 2018 ) used a hybrid dataset approach to interpret activation times during AF and Lozoya et al ( 2019 ) showed how model-based feature augmentation can help to plan the targets for ablation therapy. We developed a detailed in silico setup as a perfectly controlled testing environment to understand intracardiac signals recorded with two different commercial catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning has been extensively used in electrocardiogram analysis due to its potential to analyze big datasets and uncover mechanistic information about cardiac electrical function (Cabrera-Lozoya et al, 2017 ; Hannun et al, 2019 ; Lown et al, 2020 ; Luongo et al, 2020 ). While several studies aimed at quantifying AF mechanisms and automatically localize reentrant drivers using in silico or clinical electrograms (Schilling et al, 2015 ; McGillivray et al, 2018 ; Lozoya et al, 2019 ), less attention has been paid to the information that intracardiac electrograms can provide about the cardiac substrate based on the signal morphology due to the effect of fibrosis. Campos et al ( 2013 ) classified different types of fibrosis based on electrogram features using in silico experiments.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, physicians and offline channels of health information such as books, family and friends are not always available and have limited time. Furthermore, with the development of communication technology, there are many ways to share information (Lozoya et al, 2018). Information is presented digitally in many ways through pictures, videos, specialized applications, personalized notification, among others.…”
Section: Hypothesesmentioning
confidence: 99%
“…27 At present both of these approaches rely on explicit biophysical models derived from image segmentations, but recently this idea has been extended to use ML to select therapeutic targets; one example being the identification of sites for cardiac ablation on multi-modal imaging. 28 Sometimes cardiovascular disease classifications are straightforward and made by well-defined, if arbitrary, haemodynamic or volumetric criteria. To take two examples, pulmonary hypertension is defined by a resting mean pulmonary artery pressure of at least 25 mmHg and hypertrophic cardiomyopathy as a wall thickness of at least 15 mm that is not solely explained by abnormal loading conditions.…”
Section: Clinical Usesmentioning
confidence: 99%